BINDING EFFICACY OF YEAST SLUDGE FRACTIONS AND COMMERCIAL GLUCOMANNAN AGAINST AFLATOXINS IN BROILERS - Y. A. Ditta; Saima; T. N. Pasha; M. Akram; Z. M. Iqbal; S. Naseem (Journal of Animal and Plant Sciences, 2016)
This study was conducted to compare the efficacy of sonicated  yeast sludge fractions (Cell Wall and Cell Solubles) with commercial glucomannan against Aflatoxin B1 and G1 (AFB1 and AFG1) in feed. A total of 390 chicks were randomly divided into 13 treatments (three replicates / treatment and ten chicks / replicate). Negative control (NC) included no AFB1+AFG1 and toxin binder. The positive control contained different AFB1+AFG1 levels (100, 200 and 300 ppb of ech). Other treatments included yeast sludge fractions and organic toxin binder with AFB1+AFG1 levels. As a result of this study, depressed feed intake and body weight were observed as compared to negative control. Non-significant effect between yeast sludge cell wall and glucomannan product was observed but was significant than negative control. The aflatoxins showed significantly negative impact on weight gain, relative liver weight and serum minerals and non-significant effect on feed intake, dressing percentage and serum phosphorus. The different toxin binders showed significant effect on feed intake, weight gain, feed conversion ratio(FCR), relative liver weight, serum albumin, cholesterol and serum minerals while non-significant effect was observed on dressing percentage and serum phosphorus. The data indicated that yeast sludge cell wall showed non-significant results with commercial Glucomannan whereas Yeast Sludge Cell Soluble was showed significantly depressed effect on the production, liver and serum minerals.
Keywords: Aflatoxin; Broilers; Glucomannan; Yeast Sludge Cell Wall; Yeast Sludge Cell Soluble; Sonication